Perceptions of mothers on child well-being, changes in everyday life and social sustainability: lessons learned from a community-based health promotion programme in Anuradhapura District, Sri Lanka - Najith Duminda Galmangoda Guruge; Adam Arhelger; Kalpani Abhayasinghe (BMC, 2022)
Abstract Background From 2012 to 2015, a health promotion intervention (under a project called HADP) aiming to improve children's well-being was implemented in Horowpathana, Sri Lanka. The donor organization reports positive results regarding children's well-being and behaviour changes, but mixed results regarding its sustainability. A need for a complementary evaluation was therefore identified. The current study intended to provide a complementary evaluation at four months after the programme closure and to assess the sustainability of the HP intervention from the perspective of mothers who participated in the HADP. Ethical approval for this study was obtained from the ethics review subcommittee of Faculty of Applied Sciences, RUSL. Methods A descriptive qualitative study was carried out using in-depth, semi-structured interviews with a convenient sample of 15 mothers who previously participated in HADP. Data analysis was done using the content analysis method. Results Mothers attributed diverse perceptions in line with the theme of "health literacy". Two sub-themes emerged: transformation for betterment and sustainability. The sub-theme of transformation for betterment consists of three categories: individual-level transformation, family-level transformation and social/community-level transformation. Sub-theme sustainability consists of two categories: (1) drivers/adaptations for continuation and (2) determinants that hinder the continuation. Conclusions The mothers' perspectives were strongly related to the definition of health literacy, which emphasizes people's ability to use health information to make "well-informed" decisions that incorporate a public health perspective. They also acknowledged the responsibility of social organizations to address health literacy. From a health promotion perspective, the findings of our study indicate that people and organizations can use their health literacy skills to improve the health and well-being of their community and its members. Further research is necessary to explore the factors that affect the sustainability of health promotion interventions in the long run.